2020
DOI: 10.20944/preprints202005.0397.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Genetic Uniformity of a Specific Region in SARS-CoV-2 Genome and In-Silico Target-Oriented Repurposing of N-Acetyl-D-Glucosamine

Abstract: Causative agent of the viral pneumonia outbreak in the World identified as SARS-CoV2 leads to a severe respiratory illness like SARS and MERS. The pathogen spreading has turned into a pandemic dissemination and increased the mortality rate. Therefore, useful information is urgently necessary for effective control of the disease. Our study shows the existence of unvarying sequence with no mutation, including ORF1ab regions in 134 high-quality filtered genome sequences of SARS-CoV2 downloaded from the GISAID dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Our previous findings indicated that D-GlcNAc is a potential compound suggesting strong interaction with proteins involving the ORF1ab region. The data of our previous study showed a drastically unvarying sequence fragment in whole paired genome sequences that can be used as a target origin for designing an effective drug to SARS-CoV-2 [ 9 ]. Our results stressed that D-GlcNAc could be considered as a therapeutic option after testing its different concentrations which would be repositioned against SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our previous findings indicated that D-GlcNAc is a potential compound suggesting strong interaction with proteins involving the ORF1ab region. The data of our previous study showed a drastically unvarying sequence fragment in whole paired genome sequences that can be used as a target origin for designing an effective drug to SARS-CoV-2 [ 9 ]. Our results stressed that D-GlcNAc could be considered as a therapeutic option after testing its different concentrations which would be repositioned against SARS-CoV-2.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we have investigated unvarying regions with less mutations than the other parts of SARS-CoV-2 genome obtained from 134 different genome sequences of the GISAID database from distinct parts of the world. The amino acid sequence of the conserved region (ORF1ab region) was obtained, then subjected to homology modeling and introduced N-acetyl-D-glucosamine (D-GlcNAc) as a potential inhibitor for the selected proteins; spike receptor-binding domain bound with ACE2 (PDB 6M0J) and RNA-binding domain of nucleocapsid phosphoprotein (PDB 6WKP) from SARS-CoV-2 [ 9 ]. Previous studies have also indicated that the effectiveness of D-GlcNAc against influenza and as a starting material of oseltamivir, a purposed drug for SARS-Cov-2 treatment, D-GlcNAc has been transformed into azido group followed by implantation of a 3-pentoxy group of the desired chemical structure [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies, MAUVE analysis was conducted to gure out the stable region of the SARS-CoV-2 genome to discover the potential drug candidates matching proteins playing a role in its virulence [14][15][16].…”
Section: Introductionmentioning
confidence: 99%